History taking and response to an adult diarrheal case among community drug retail outlets in Gondar town, north-west Ethiopia: a simulated-client survey - Dawit Wondimsigegn; Berhanemeskel Woldegerima; Asefa Adimasu Taddese (Taylor & Francis Group, 2021)
Background Self-care is one of the growing tasks of community pharmacy professionals. They are highly engaged in consultations in response to specific drug request (product-based presentation) or symptoms clients describe (symptom-based presentation). Purpose This study was aimed at assessing the appropriateness of patient assessment and response to an adult diarrheal case among community drug retail outlets in Gondar town, north-west Ethiopia. Methods A descriptive cross-sectional study design based on simulated-client method of visit was conducted from 03 August to 21 September, 2020. An adult female diarrheal case scenario was developed and used to guide data collectors to interact with professionals in a standardized and consistent way. All 60 dispensaries in the town during the data collection were included in the study. A pretested data collection tool was used to record the conversation between simulated clients and providers. The data were analyzed using SPSS version 20. Results With regard to patient history, age of the patient, whether diarrhea is watery or bloody and onset and duration of diarrhea were the three most commonly requested questions with 59 (98.3%), 55 (91.7%) and 46 (76.7%), respectively. Past-medical and medication history are enquired in none of the visits. Medication was dispensed in 57 (95%) of the visits and no referral to a health facility was recommended in majority (90%) of cases. The most commonly recommended medications were ciprofloxacin 30 (52.6%) and metronidazole 20 (35.1%). ORS was considered in only 6 (10.5%) dispensaries. Conclusion Patient assessment, final decisions and treatment recommendations for an adult diarrheal case are inadequate, irrational and illegal. Educational interventions coupled with incentive mechanisms for cognitive pharmaceutical service and strict regulatory enforcement are needed to reduce the problem.